2015
DOI: 10.1002/soej.12068
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous gender effects under loss aversion in the economics classroom: A field experiment

Abstract: This article evaluates the impact of loss aversion as a behavioral motivator on students classroom performance. Conducting an experiment with University of Kentucky undergraduate students, the authors framed student grades as a loss and gain. In treatment sections, the students began with full marks and lost points as the semester progressed, whereas in control sections, under a traditional grading scheme, students accumulated points throughout the semester. We find that treated individuals, on average, do not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 25 publications
0
20
1
Order By: Relevance
“…McEvoy (2016) on the other hand reported no gender effects in a similar study also testing a loss framing for grade points earned by US university students. In contrast to Apostolova-Mihaylova et al (2015) and McEvoy (2016) found positive effects on grades and the likelihood of attempting the final exam when controlling for individual specific characteristics. The effect of the loss frame appeared most important for assignments at the end of the semester.…”
Section: Framingmentioning
confidence: 73%
“…McEvoy (2016) on the other hand reported no gender effects in a similar study also testing a loss framing for grade points earned by US university students. In contrast to Apostolova-Mihaylova et al (2015) and McEvoy (2016) found positive effects on grades and the likelihood of attempting the final exam when controlling for individual specific characteristics. The effect of the loss frame appeared most important for assignments at the end of the semester.…”
Section: Framingmentioning
confidence: 73%
“…In the course of this investigation we also determined whether our data set showed evidence of a heterogeneous-sex effect from the loss aversion treatment when controlling for student ability, as was found in Apostolova-Mihaylova et al (2015). This can be stated as our second hypothesis:…”
Section: The Present Studymentioning
confidence: 83%
“…The differential impact of the Treatment ؋ Sex specification. The work of Apostolova-Mihaylova et al (2015) indicated that female students might perform worse under the inverted grading method, compared to the male students. Using our data set, we were interested in replicating this result.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Levitt et al (2016) also find some evidence that students respond more to rewards framed as losses. Of greatest relevance to the design of our assessment, Apostolova-Mihaylova et al (2015) find that framing the grading system in terms of losses leads to better outcomes, though only for males. Women in the study performed worse under the loss aversion frame.…”
Section: Loss Aversion and Peer Assessmentmentioning
confidence: 97%